The paradoxes of public space - Marcuse, Peter (Journal of Architecture and Urbanism, 2014)
This paper deals with one particular purpose for public space, the role it plays in permitting popular public participation in in democratic governance, democratic governance in a very political sense. For the United States, it might be called “First Amendment Space”, after the provision in the U.S.A. Constituting establishing the rights of free speech and free assembly. In a broader sense, public space should also be available democratically and based on equality of rights for a full range of social interchanges, for recreation, sports, picnicking, hiking, running, sitting, chatting, simply enjoyment, by all people, equally. Such uses, carried out democratically, are in turn necessary for democratic governance, but in a different way. Let me call them “Social Spaces”. And they may be divided between Convening spaces, where convening for the purposes of political effectiveness may be planned, and Encounter Spaces, where chance meetings and discussion may be take place without prior planning/convening. “Infrastructural Spaces” are also social spaces but in a different sense, not directly political: spaces for transportation, streets, sidewalks, recreational areas, parks, hiking trails, bicycles partially. he term “Third Space” is sometimes in fashion in a similar sense, and often defined as somewhere between public and private1. More on social spaces elsewhere. When public space is referred to here, it is in the sense of political public space, First Amendment space in the United States. Tahrir Square in Cairo, the Playa of Mothers in Buenos Aires, the Mall in Washington, D.C., Zuccotti Park in New York City, perhaps Central Park or Fifth Avenue, with its parades and marches, but also the fenced in space under the West Side highway at the time of the Republican Convention, and perhaps the indoor space of the Convention Center, as used for convening for discussions of alternate proposals for rebuilding after 9/11.